"Appropriately homeless and needy:" Examining street homeless survival through the lens of Bourdieusian social capital theory. Issue 7 (2nd October 2020) - Cook, Shelley; Hole, Rachelle
ABSTRACT: This research explores street homeless people's survival in the urban realm through their relationship with the system of homelessness services. Given the growing numbers and complexity of street homeless and their related health and social needs, and the increased competition for essential, life-sustaining resources, we examine how street homeless people get their support needs met through their social capital interactions with homelessness service providers. We use Pierre Bourdieu's social capital and related theory as the conceptual framework for inquiry. Qualitative participatory mapping methods were used. Twenty-nine street homeless individuals participated in individual mapping interviews. Interview transcripts were thematically coded using NVivo qualitative data analysis software. Member checking was used to validate emerging themes with the Advisory Committee throughout the data analysis process. All participants had extremely low levels of social capital and all were dependent on homelessness services for their basic needs. To acquire social capital through institutional sources they depend upon for survival, street homeless people perform representations of homeless identity to align with the discourse on homelessness being promoted through the service context. Through their performances, there was a tendency to play up vulnerabilities or deficits. Findings are discussed in relation to the implications for practice.